Diarrhoea in travellers. (January 2018) - Barrett, Jessica; Brown, Mike
Abstract: Travellers' diarrhoea is a common illness, particularly among travellers visiting low-income countries, and is generally self-limiting and uncomplicated. However, it has a disproportionate impact on well-being, occurring as it does during holidays or business trips, and can result in severe dehydration. Most causes of acute travellers' diarrhoea are bacterial or viral, and the pathogen is often not identified, either because the illness resolves too quickly, or because medical attention is sought only after a delay. Parasites are a more important cause of chronic diarrhoea after travel; however, the most common reason for continuing symptoms is post-infectious irritable bowel syndrome. Here we review the epidemiology and causative organisms, and provide a rationale for the investigation and treatment of both acute and chronic travel-associated diarrhoea.